Frequency and Significance of Abnormal Pancreatic Imaging in Patients with BRCA1 and BRCA2 Genetic Mutations - Elie Chahla; Antonio Cheesman; Suzanne M. Mahon; Robert W. Garrett; Ben P. Bradenham; Theresa L. Schwartz; Louay Omran; Jason R. Taylor; Samer Alkaade (Scientifica)
Objective. Pancreatic adenocarcinoma is typically diagnosed in advanced stages resulting in a significant reduction in the number of patients who are candidates for surgical resection. Although the majority of cases are believed to occur sporadically, about 10% show familial clustering and studies have identified an increased frequency of BRCA germline mutations. The role of screening for pancreatic adenocarcinoma in these populations is unclear. Our study aims to identify the abnormal pancreatic imaging findings in BRCA1 and BRCA2 mutation carriers. Methods. A retrospective review of patient medical records with known BRCA1 and BRCA2 mutations was conducted. Data was collected and all available abdominal imaging studies were reviewed. Results. A total of 66 patients were identified, 36 with BRCA1 and 30 with BRCA2 mutations. Only 20/66 (30%) had abdominal imaging (14 BRCA1 and 6 BRCA2 patients). Of those patients with abdominal imaging, abnormal pancreatic imaging findings were detected in 7/20 (35%) cases. Conclusion. Our study shows a high incidence of abnormal pancreatic imaging findings in patients with BRCA genetic mutations (35%). Larger studies are needed to further define the role of pancreatic cancer screening and the significance of abnormal imaging findings in BRCA1 and BRCA2 mutation carriers.